Faktor-Faktor Penentu Minat Generasi Z dalam Penggunaan Buy Now Paylater pada Mahasiswa Universitas Dian Nuswantoro Semarang - Tharisya Alvita Cahyarani; Vicky Oktavia; Ariati Anomsari; Almira Santi Samasta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to identify the factors influencing the interest of Universitas Dian Nuswantoro students in using Buy Now Pay Later (Paylater) services. The research focuses on three aspects: Perceived Ease of Use, Functional Financial Needs, and Hedonistic Lifestyle. The method employed is descriptive quantitative research with a survey approach. The study involved 160 students who had previously used Paylater services. The collected data were analyzed using SmartPLS 4 software, examining validity, reliability, and structural model tests. The results indicate that Hedonistic Lifestyle positively and significantly affects the intention to use Paylater, followed by Functional Financial Needs, which also have a significant influence. Meanwhile, Perceived Ease of Use does not have a significant effect, as young people, particularly Generation Z, are already very familiar with various digital applications, making operational ease not a primary factor. The study concludes that students’ interest in using Paylater is more influenced by their consumption patterns and financial needs rather than the technical aspects of the system. Based on these findings, several recommendations are offered: to enhance education on the responsible use of Paylater services and to provide clear information about the services so that users can manage their expenses more effectively.